1977
DOI: 10.1172/jci108827
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Prostaglandin E in Defective Insulin Secretion and Carbohydrate Intolerance in Diabetes Mellitus

Abstract: A B S T R A C T Prostaglandin E2 (PGE2) infusion in normal humans inhibited acute insulin responses to a glucose (5 g i.v.) pulse (response before PGE2 = 593 + 104%; during PGE2 = 312+55%, mean+SE, mean change 3-5 min insulin, % basal, P < 0.005). This effect was associated with a decrease in glucose disappearance rates (KG before PGE2= 0.73+0.07; during PGE2= 0.49+0.06 %/min, P < 0.025). Acute insulin responses to arginine (2 g i.v.) were not affected by PGE2 (response before PGE2 = 592+164%; during PGE2 = 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 154 publications
(79 citation statements)
references
References 19 publications
4
75
0
Order By: Relevance
“…These events lead to increased synthesis of PGE 2 and EP3 receptor protein. Binding of PGE 2 to EP3 has been shown by us to decrease islet cAMP levels (27), thereby decreasing glucose-induced insulin secretion. Interference with these events by sodium salicylate occurs at the site of IL-1␤ activation of NF-B and of COX-2 enzymatic activity.…”
Section: Sodium Salicylate Cox-2 Ep3 Receptor and Insulin Secretionmentioning
confidence: 97%
See 2 more Smart Citations
“…These events lead to increased synthesis of PGE 2 and EP3 receptor protein. Binding of PGE 2 to EP3 has been shown by us to decrease islet cAMP levels (27), thereby decreasing glucose-induced insulin secretion. Interference with these events by sodium salicylate occurs at the site of IL-1␤ activation of NF-B and of COX-2 enzymatic activity.…”
Section: Sodium Salicylate Cox-2 Ep3 Receptor and Insulin Secretionmentioning
confidence: 97%
“…Sodium salicylate has been known for Ͼ30 years to be an inhibitor of COX activity (44,45) and has been demonstrated to improve defective insulin secretion in patients with diabetes (2,46,47). This drug has been reported to inhibit dissociation of NF-B from NF-B/IB complexes (17,18), thereby preventing transport of NF-B from the cytoplasm to the nucleus of cells, where it stimulates COX-2 and EP receptor transcription (19,20).…”
Section: Sodium Salicylate Cox-2 Ep3 Receptor and Insulin Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, both prostaglandin E2 and prostacyclin synthesis are thought to have an adaptive role in the reduction of high blood pressure in patients with diabetes through increased COX-2 expression resulting in vasodilation [10], as well as playing a cardio protective role [11]. COX-2 also contributes to insulin signalling, as prostaglandin E2 in pancreatic β-cells has a negative effect on insulin secretion [12,13]. It is clear that COX-2 regulates a number of key pathways producing paracrine hormones with a range of physiological functions and has the potential to be a therapeutic to prevent cardiovascular disease [14].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of indomethacin on residual insulin secretion was also assessed by measuring C-peptide plasma levels during the arginine infusions. Indeed, Robertson and his group [2,22,26] have reported that blocking the synthesis of prostaglandins by sodium salicylate intravenous infusion improved the insulin response to glucose in Type 2 (insulin independent) diabetics. In addition we attempted to correlate the magnitude of the blood glucose rise induced by arginine infusion with the insulin-secretory reserve and the amplitude of the glucagon rise.…”
mentioning
confidence: 99%